A diferenciação entre direito e moral na tradição do positivismo jurídico - Froehlich, Charles Andrade (2017)
The present thesis intends to defend, mainly, the possibility of differentiation between Law and Moral proposed by the tradition of legal positivism. In this way, we will defend what is now called ―exclusive legal positivism‖. In a second moment, the ―normative‖ view will be added to this positivism. For contemporary legal positivists, it is true that the separation thesis does not mean that law does not have connections, necessary or not, to morality. What the contemporary legal positivists assert is that the existence and validity of law can not depend on moral criteria. The existence and validity of law depend only on social facts. Which brings us to the question of the sources of law. We will affirm, therefore, that the thesis that conjugates or names legal positivism is the thesis of social sources of law. The separation thesis is at best a sub-thesis of legal positivism. The first chapter deals with the ―Evolution of Legal Positivism‖, seeking to trace a historical course of the debate between law and morals and the characterization and changes of the two main schools of legal thinking: natural law theory and legal positivism. Thus, we begin with the reference to Greek culture and we come to the current debate between inclusivists and exclusivists. The second chapter delves deeper into the first in some ways. It deals specifically with the ―Challenges of Legal Positivism‖, that is, the arguments of its main opponent - Ronald Dworkin - as well as the counter-arguments and renewal of legal positivism in the new currents that have been established: exclusive legal positivism, inclusive legal positivism and (exclusive) normative legal positivism. The third chapter is the broadest and addresses ―The relationship between law and morality‖ from both the analytical and normative perspectives. It seeks from the influences of the first utilitarians on legal positivism, going through the importance of the distinction between positive moral and critical moral and ending with the replacement of the problem of the separation of law and moral in legal positivism. Finally, according to the arguments of exclusive legal positivism, especially the practical difference thesis, we opt for the best formulation that appears in the title of this thesis: the differentiation between law and morality from the sources thesis.